Pharmacological and Advanced Cell Respiration Effects, Enhanced by Toxic Human-Bile Nano-Pharmaceuticals of Probucol Cell-Targeting Formulations - Susbin Raj Wagle; Bozica Kovacevic; Daniel Walker; Corina Mihaela Ionescu; Melissa Jones; Goran Stojanovic; Sanja Kojic; Armin Mooranian; Hani Al-Salami (MDPI AG, 2020)
Bile acids have recently been studied for potential applications as formulation excipients and enhancers for drug release; however, some bile acids are not suitable for this application. Unconjugated lithocholic acid (ULCA) has recently shown drug formulation-stabilizing and anti-inflammatory effects. Lipophilic drugs have poor gut absorption after an oral dose, which necessitates the administration of high doses and causes subsequent side effects. Probucol (PB) is a highly lipophilic drug with poor oral absorption that resulted in restrictions on its clinical prescribing. Hence, this study aimed to design new delivery systems for PB using ULCA-based matrices and to test drug formulation, release, temperature, and biological effects. ULCA-based matrices were formulated for PB oral delivery by applying the jet-flow microencapsulation technique using sodium alginate as a polymer. ULCA addition to new PB matrices improved the microcapsule's stability, drug release in vitro (formulation study), and showed a promising effect in ex vivo study (p < 0.05), suggesting that ULCA can optimize the oral delivery of PB and support its potential application in diabetes treatment.